2018
DOI: 10.24815/jdab.v5i1.8623
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control, Penerimaan Auditor atas Dysfunctional Audit Behavior dan Intention to Quit

Abstract: More specifically, it aims to investigate locus of control on intention to quit and auditor acceptance of dysfunctional audit behavior. This study surveys public accounting firm in Sumatera with a total of107 respondents. Data analysis was performed by using Structural Equation Modeling-Partial Least Square (PLS-SEM). The results show that locus of control has positive influence on intention to quit and auditor acceptance of dysfunctional audit behavior. In addition, it is also suggested that the effect of loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…the premature sign-off. A four-item of dysfunctional audit behavior instrument was adopted from Donnelly et al (2003) and tested by Paino et al (2012), Herda and Martin (2016) and Anita et al (2018) to measure the level of auditor’s acceptance toward dysfunctional audit behavior. The scale used for this measurement ranged from 1 to 5, in which “1” indicated strongly disagree and “5” indicated strongly agree.…”
Section: Methodsmentioning
confidence: 99%
“…the premature sign-off. A four-item of dysfunctional audit behavior instrument was adopted from Donnelly et al (2003) and tested by Paino et al (2012), Herda and Martin (2016) and Anita et al (2018) to measure the level of auditor’s acceptance toward dysfunctional audit behavior. The scale used for this measurement ranged from 1 to 5, in which “1” indicated strongly disagree and “5” indicated strongly agree.…”
Section: Methodsmentioning
confidence: 99%
“…Suatu konstruk dikatakan reliabel jika nilai Cronbach's alpha harus lebih dari 0,6 dan nilai composite reliability harus lebih dari 0,6. (Anita, Nanda, Zenita, & Abdillah, 2018). Rule of thumbs untuk uji reliabilitas dengan indikator reflektif dapat dilihat dalam tabel 1.…”
Section: Hasilunclassified
“…The research of Sipayung et al (2021), found that external locus of control tended to be related to the behavior of decreasing audit quality. This is reinforced by research conducted by Anita et al (2018), which found that there is a positive relationship between individuals and external locus of control with deviant behavior or cheating to achieve personal goals. Individuals who have an external locus of control tend to not believe in their own abilities so they have the potential to try to manipulate colleagues or other objects to maintain their position.…”
Section: Introductionmentioning
confidence: 97%
“…The behavior of reducing audit quality includes premature sign-off, making a shallow review of client documents, accepting client explanations that are not strong, ignoring the accounting principles applied by the client, and not conducting further testing on doubtful items. Meanwhile, dysfunctional behavior that indirectly reduces audit quality is called under-reporting of time behavior (Anita et al, 2018). Under-reporting of time (URT) is the behavior of auditors who report audit results that are not in accordance with the actual time used or report audit results that are shorter than the actual time used in conducting the audit.…”
Section: Introductionmentioning
confidence: 99%